Ecology of Fear: Spines, Armor and Noxious Chemicals Deter Predators in Cancer and in Nature - Peplinski, Joy; Malone, Margaret A.; Fowler, Katherine J.; Potratz, Emily J.; Pergams, Alexander G.; Charmoy, Kristie L.; Rasheed, Kiran; Avdieiev, Stanislav S.; Whelan, Christopher J.; Brown, Joel S. (Frontiers in Ecology and Evolution, 2021)
In nature, many multicellular and unicellular organisms use constitutive defenses such as armor, spines, and noxious chemicals to keep predators at bay. These defenses render the prey difficult and/or dangerous to subdue and handle, which confers a strong deterrent for predators. The distinct benefit of this mode of defense is that prey can defend in place and continue activities such as foraging even under imminent threat of predation. The same qualitative types of armored, spiny, and noxious defenses have evolved independently and repeatedly in nature, and we present evidence that cancer is no exception. Cancer cells exist in environments inundated with predator-like immune cells, so the ability of cancer cells to defend in place while foraging and proliferating would clearly be advantageous. We argue that these defenses repeatedly evolve in cancers and may be among the most advanced and important adaptations of cancers. By drawing parallels between several taxa exhibiting armored, spiny, and noxious defenses, we present an overview of different ways constitutive defenses can appear and emphasize how phenotypes that appear vastly different can nevertheless have the same essential functions. This cross-taxa comparison reveals how cancer phenotypes can be interpreted as antipredator defenses, which can facilitate therapy approaches which aim to give the predators (the immune system) the upper hand. Furthermore, cancer systems are microcosms in which evolutionary ecologists can observe how prey evolve in response to nontraditional predators which are neither driven by individual gain nor deterred by individual danger.